On the dark matter distribution in the Milky Way - Iocco, Fabio [UNESP]; Pato, Miguel (IOP Publishing, 2016)
The distribution of dark matter in the Milky Way is a crucial input for ongoing studies in cosmology, astrophysics and particle physics. This motivates the effort over the next years to improve our mapping of dark matter, which has indeed become a top priority in the field. We report briefly on the state of the art regarding the dark matter distribution in our Galaxy, with a special emphasis in the inner part of the Galaxy where baryons start to give an important dynamical contribute to the total gravitational potential. After introducing the kinematic data used to trace the rotation curve and the photometric data used to model the different baryonic components, we combine kinematics and photometry to single out the dark matter content. The procedure is then used to assess the evidence for dark matter and to constrain the underlying dark matter distribution with two conceptually distinct approaches, which we dub profile fitting and profile reconstruction. Finally, in view of the swarm of astronomical data soon to become available, we shortly address the expected progress in pinpointing dark matter across the Galaxy.